Gene editing in monogenic autism spectrum disorder: animal models and gene therapies - Wang, Na; Lv, Longbao; Huang, Xiaoyi; Shi, Mingqin; Dai, Youwu; Wei, Yuanyuan; Xu, Bonan; Fu, Chenyang; Huang, Haoyu; Shi, Hongling; Liu, Yun; Hu, Xintian; et al. (Frontiers in Molecular Neuroscience, 2022)
Autism spectrum disorder (ASD) is a lifelong neurodevelopmental disease, and its diagnosis is dependent on behavioral manifestation, such as impaired reciprocal social interactions, stereotyped repetitive behaviors, as well as restricted interests. However, ASD etiology has eluded researchers to date. In the past decades, based on strong genetic evidence including mutations in a single gene, gene editing technology has become an essential tool for exploring the pathogenetic mechanisms of ASD via constructing genetically modified animal models which validates the casual relationship between genetic risk factors and the development of ASD, thus contributing to develop ideal candidates for gene therapies. The present review discusses the progress in gene editing techniques and genetic research, animal models established by gene editing, as well as gene therapies in ASD. Future research should focus on improving the validity of animal models, and reliable DNA diagnostics and accurate prediction of the functional effects of the mutation will likely be equally crucial for the safe application of gene therapies.